2020
DOI: 10.1371/journal.pone.0232633
|View full text |Cite
|
Sign up to set email alerts
|

Neighboring plants divergently modulate effects of loss-of-function in maize mycorrhizal phosphate uptake on host physiology and root fungal microbiota

Abstract: Maize, a main crop worldwide, establishes a mutualistic symbiosis with arbuscular mycorrhizal (AM) fungi providing nutrients to the roots from soil volumes which are normally not in reach of the non-colonized root. The mycorrhizal phosphate uptake pathway (MPU) spans from extraradical hyphae to root cortex cells housing fungal arbuscules and promotes the supply of phosphate to the mycorrhizal host in exchange for photosynthetic carbon. This symbiotic association with the mycobiont has been shown to affect plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
1
6
1
Order By: Relevance
“…We found that the root lipid status between wild-type and AMF-deficient pht1 ; 6 plants differed more strongly under NK than under NPK conditions, which is likely linked to perturbed cross-kingdom lipid transfer from the host to AMF in the mutant roots. We also observed that the performance of pht1 ; 6 mutants was reduced compared to that of the wild type, as previously shown ( 40 , 60 ), and more severely at the vegetative growth phase. These performance differences were partially compensated for at the reproductive growth phase under P-sufficient conditions (NPK).…”
Section: Discussionsupporting
confidence: 89%
“…We found that the root lipid status between wild-type and AMF-deficient pht1 ; 6 plants differed more strongly under NK than under NPK conditions, which is likely linked to perturbed cross-kingdom lipid transfer from the host to AMF in the mutant roots. We also observed that the performance of pht1 ; 6 mutants was reduced compared to that of the wild type, as previously shown ( 40 , 60 ), and more severely at the vegetative growth phase. These performance differences were partially compensated for at the reproductive growth phase under P-sufficient conditions (NPK).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, because the relative effect of host genetics on the microbiota can highly depend on the plant habitat, in particular the inoculum source (e.g. agricultural soil) (Robertson-Albertyn et al 2017; Hubbard et al 2018; Fabiańska et al 2020), setting up genetic association studies in a common garden can bring to partial conclusions on the host genetics controlling for microbiota (Oyserman et al 2020). One approach to tackle these issues is to conduct Genome-Environment Association (GEA) analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, our current understanding on plant–plant interactions mediated by microorganisms is still very limited. A recent study suggests that maize plants trigger AM fungal colonization in mutant neighboring plants displaying deficiency in the mycorrhizal Pi uptake pathway, through nutrient delivery to the CMN (Fabianska et al, 2020 ). This example opens interesting perspectives for the selection of genotypes that invest in the CMN.…”
Section: Conclusion Challenges and Future Directions For Promoting Be...mentioning
confidence: 99%